Балансування навантаження в інфокомунікаційних мережах на принципах Traffic Engineering: рішення та приклади - Крепко, А. В.; Стаднік, В. В. (ХНУРЕ, 2023)
The paper reviews solutions for applying the Traffic Engineering concept to load balancing in infocommunication networks. A common feature of the reviewed solutions is the use of an optimization approach to solving load-balancing problems. The solutions cover the routing area - unicast, multicast, fault-tolerant, secure, and priority-based queue management. Such solutions aim to improve the Quality of Service and fault tolerance in infocommunication networks.
Keywords: Traffic Engineering; балансування навантаження